New Age Gathering in a Pandemic: European Rainbow Gathering 2021 in France - Ratia, Katri (Nova religio, 2023)
Rainbow Gatherings are alternative grassroots events that are held as weeks-long camps in natural settings. The Gatherings can be described as temporary intentional communities and transformational events, advocating many central ideals of Western counterculture and alternative-holistic spirituality, inter alia, by employing radical alternatives to market economy, centralized leadership, and religious institutions. These non-commercial and nonviolent Gatherings are fully inclusive and participatory, and before the onset of the COVID-19 pandemic, there were dozens of events in Europe annually. The essay depicts how the pandemic and related restrictions were experienced and interpreted among the participants of the 2021 European Rainbow Gathering and describes relevant aspects of the underlying religious and cultural context. The essay connects the observations to recent research on "conspirituality" in its contexts of cultural views, expression, and practices.